KARAKTERISTIK ODHA YANG BERKUNJUNG KE KLINIK VCT DI RSUP H. ADAM MALIK MEDAN TAHUN 2014 - muhammad syahreza; Sori Muda Sarumpaet; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT HIV/AIDS is infectious disease that already became worldwide pandemic. According to ministry of health of Indonesia’s Republic, the number of cases of HIV/AIDS which has report from 1st January to 30th June 2014, about 15,534 HIV cases and 1,700 AIDS cases. This study is descriptive by using case series design. The population were 602 outpatients of HIV/AIDS in RSUP H. Adam Malik Medan in 2014. The sample size were 100 cases by using simple random sampling. The data analysis uses a secondary data by using Chi-Square and Fisher’s Exact. The results of this research  showed that the highest proportion of patient with HIV/AIDS was at the age 30-39 years old is male (33%) and female (18%), Batak (52%), High School (55%), private employee (52%), married (42%), outside Medan city (56%), heterosexual (80%),long time identified < 2 years (49%),long time consumes ARV 1-2 years (42%). According to the statistical test with Exact Fisher, there was  no significant differences between proportion of gender with risk factor (p=0,304) and job with risk factor (p=0,304). It is expected for PUSYANSUS VCT RSUP H. Adam Malik Medan to fulfilled patients data form in status card. Also to all the HIV/AIDS patients in PUSYANSUS VCT RSUP H. Adam Malik Medan to prevent the transmission of HIV/AIDS by faithful with the partner and also consisstant to use birth control while having sex to avoid the transmission of HIV/AIDS and/ or STD to the healthy partner and also who are already infected of HIV/AIDS and/ or STD.   Keywords : HIV/AIDS, Characteristic, RSUP H. Adam Malik Medan